Should Animals Navigating Over Short Distances Switch to a Magnetic Compass Sense? - Wyeth, Russell (Frontiers in Behavioral Neuroscience, 2010)
Magnetoreception can play a substantial role in long distance navigation by animals. I hypothesize that locomotion guided by a magnetic compass sense could also play a role in short distance navigation. Animals identify mates, prey or other short distance navigational goals using different sensory modalities (olfaction, vision, audition, etc.) to detect sensory cues associated with those goals. In conditions where these cues become unreliable for navigation (due to flow changes, obstructions, noise interference, etc.), switching to a magnetic compass sense to guide locomotion towards the navigational goals could be beneficial. Using simulations based on known locomotory and flow parameters, I show this strategy has strong theoretical benefits for the nudibranch mollusc Tritonia diomedea navigating towards odour sources in variable flow. A number of other animals may garner similar benefits, particularly slow-moving species in environments with rapidly changing cues relevant for navigation. Faster animals might also benefit from switching to a magnetic compass sense, provided the initial cues used for navigation (acoustic signals, odours, etc.) are intermittent or change rapidly enough that the entire navigation behaviour cannot be guided by a continuously detectable cue. Examination of the relative durations of navigational tasks, the persistence of navigational cues, and the stability of both navigators and navigational targets will identify candidates with the appropriate combination of unreliable initial cues and relatively immobile navigational goals for which this hypothetical behaviour could be beneficial. Magnetic manipulations can then test whether a switch to a magnetic compass sense occurs. This hypothesis thus provides an alternative when considering the behavioural significance of a magnetic compass sense in animals.